Validation of diagnostic screening test for pharmacogenomic targets for thiopurine drugs in indian pediatric acute lymphoblastic leukemia patients - Joseph, Gratial Theres; Swain, Sandeep Kumar; Somwanshi, Tejas; Singh, Aarishi; Kaur, Manpreet; Kamal, Raj; Dhanda, Himanshu; Kumar, Prashant; Kaushik, Upasana; Noor, Baseer; Sharma, Saurabh; Tanwar, Pranay; et al. (Frontiers in Pharmacology, 2025)
BackgroundThiopurines such as 6-mercaptopurine (6-MP) are central to maintenance therapy for pediatric acute lymphoblastic leukemia (ALL), yet their narrow therapeutic index frequently causes dose-limiting myelosuppression in genetically susceptible patients. Variants in NUDT15 and TPMT are major pharmacogenetic determinants of thiopurine intolerance, particularly in Asian populations. Despite CPIC recommendations for pre-emptive genotyping, routine pharmacogenetic testing is seldom implemented in India due to high costs and limited access to sequencing-based platforms.AimTo develop, standardize, and validate a rapid, low-cost tetra-primer ARMS-PCR assay for simultaneous detection of the most clinically relevant variants—NUDT15 c.415C>T and TPMT 3C (c.719A>G)—prioritized through comprehensive in silico analysis.MethodsMissense SNPs in NUDT15 and TPMT were screened using SIFT, PolyPhen-2, PROVEAN, Meta-SNP, and SNPs&GO to identify high-impact variants. A multiplex ARMS-PCR assay was optimized and applied to 61 pediatric ALL samples. Genotyping results were validated by Sanger sequencing. Clinical correlations included hematologic toxicity, 6-MP dose intensity, and blast-percentage dynamics.ResultsIn-silico prioritization consistently identified NUDT15 c.415C>T and TPMT 3C as the most deleterious and clinically actionable variants. Among 60 successfully genotyped patients, NUDT15 variants were detected in 16.7% (9 C/T and 1 T/T), while TPMT 3C heterozygosity was observed in 3.3%; no double-mutants were identified. ARMS-PCR showed 98.4% overall diagnostic accuracy relative to Sanger sequencing (sensitivity 90.9%, specificity 100%). NUDT15-variant carriers exhibited significantly reduced 6-MP dose intensity (median 0.50 vs. 0.79; p < 0.0001). Blast-percentage analysis demonstrated marked reduction from baseline to follow-up (median 75%–15%; p = 0.0001), consistent with expected treatment response.ConclusionThe validated ARMS-PCR assay provides a reliable, rapid, and cost-effective platform for simultaneous NUDT15 and TPMT 3C genotyping, demonstrating strong concordance with sequencing and clear clinical relevance. Its affordability and minimal infrastructure requirements make it suitable for integration into routine pre-treatment workflows in India, enabling genotype-guided thiopurine dosing and reducing the risk of treatment-related toxicity. This assay supports a scalable path toward equitable implementation of pharmacogenomics in resource-limited pediatric oncology settings.